Effects of Echinacea extract on the performance, antibody titres, and intestinal histology of layer chicks - KARTAL, MURAT; Gurbuz, E.; Balevi, T.; Kurtoglu, V.; Coskun, B.; Oznurlu, Y.; Kan, Y.; Kartal, MURAT (My University, 2010)
1. This research was conducted to determine the effect of diet supplementation with Echinacea extract (cichoric acid) on the growth performance, antibody titres and intestinal tissue histology of layer chicks. 2. White, 1-d-old, Hy-Line hybrid chicks (n = 540) were divided into three treatments, each consisting of 6 groups of 30 chicks (n = 180): (1) control; (2) 2 center dot 5 mg/kg cichoric-acid-fed; and (3) 5 mg/kg cichoric-acid-fed. The trial lasted 60 d. 3. While the growth performance of the chicks was depressed between d 1 and 45, it was found to improve between d 45 and 60. 4. Feed consumption was lower in both of the cichoric-acid-fed groups than in the control group between d 1-15 and 15-30, but was higher between d 30 and 45. Overall, mean feed consumption did not differ between the control and cichoric-acid-fed groups during the 60 d study period. 5. During the 60 d evaluation period, live weight gain, feed utilisation rate and final live weight were higher in the control group than in both of the cichoric-acid-fed groups. 6. Antibody titres against infectious bronchitis and infectious bursal disease did not differ between the three groups, but those for Newcastle disease were higher in the 2 center dot 5 mg/kg cichoric-acid-fed group than in the control group after 45 d. 7. Height and width of the jejunal villus and the thickness of the muscle layer were lower in the 5 mg/kg cichoric-acid-fed group than in both the control and the 2 center dot 5 mg/kg cichoric-acid-fed groups. The height of the ileal villus was also lower in the 5 mg/kg cichoric-acid-fed group than in the other two groups. 8. Echinacea extract supplementation for layer chicks appears not to benefit growth performance and intestinal histology during the growing period.